2008
DOI: 10.4142/jvs.2008.9.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of renal dimension and resistive index in clinically healthy Korean domestic short-hair cats

Abstract: Renal length, height, width, resistive index (RI), size of cortex, and medulla were determined by renal ultrasonography in 50 healthy Korean domestic short-hair cats. In the sagittal plane, the renal length was 3.83 ± 0.51 cm (mean ± SD) in the left kidney and 3.96 ± 0.48 cm in the right kidney, whereas the renal height was 2.42 ± 0.27 cm in the left kidney and 2.36 ± 0.28 cm in the right kidney. In the transverse plane, the renal height was 2.42 ± 0.28 cm in the left kidney and 2.38 ± 0.27 cm in the right kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
46
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 10 publications
13
46
3
2
Order By: Relevance
“…Previous ultrasonographical studies have reported that the normal size of the feline kidney varies between 3.0 and 4.3cm, and can even be up to 5.3cm (Walter et al, 1987, Park et al, 2008. The result obtained in Ragdoll cats (Debruyn et al, 2013) of 3.83 ± 0.45cm (range 2.98-5.09) fits well within this interval and corresponds with the renal length found by Park et al (2008) in healthy Korean domestic shorthair cats. The results of the authors above are similar to that observed in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Previous ultrasonographical studies have reported that the normal size of the feline kidney varies between 3.0 and 4.3cm, and can even be up to 5.3cm (Walter et al, 1987, Park et al, 2008. The result obtained in Ragdoll cats (Debruyn et al, 2013) of 3.83 ± 0.45cm (range 2.98-5.09) fits well within this interval and corresponds with the renal length found by Park et al (2008) in healthy Korean domestic shorthair cats. The results of the authors above are similar to that observed in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Such findings may simply reflect the varied nature of the species and breed studies' inherent physiological qualities (Rawashdeh et al, 2001). Renal dimensions and intrarenal RI have been correlated to the body weight of cats (Park et al, 2008). Studies comping with the age-intrarenal RI relationship and renin-angiotension-7 aldosterone system are limited.…”
Section: Animalsmentioning
confidence: 99%
“…To determine the renal vascular resistance, resistive index (RI), determined by Doppler ultrasonography, is applied. In this view, increased RI values suggest a renal disease [14,15]. The renal arterial RI is defined as the ratio of the difference between maximum and minimum (end diastolic) flow velocity derived from the Doppler spectrum of intrarenal (segmental/interlobar) arteries.…”
Section: Introductionmentioning
confidence: 99%